2020
DOI: 10.3389/fnbot.2020.604426
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing Five Motor Behaviors in a Salamander Robot With Virtual Muscles and a Distributed CPG Controller Regulated by Drive Signals and Proprioceptive Feedback

Abstract: Diverse locomotor behaviors emerge from the interactions between the spinal central pattern generator (CPG), descending brain signals and sensory feedback. Salamander motor behaviors include swimming, struggling, forward underwater stepping, and forward and backward terrestrial stepping. Electromyographic and kinematic recordings of the trunk show that each of these five behaviors is characterized by specific patterns of muscle activation and body curvature. Electrophysiological recordings in isolated spinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 102 publications
(180 reference statements)
3
23
0
Order By: Relevance
“…The salamander constitutes a model animal for focusing on the following two issues, representing an evolutionary process of moving from water to land: 1) versatile behavior generation against a changing environment, based on CPGs coordinated by both descending signals and sensory feedback; and 2) body-limb coordination, i.e., coordination between undulatory movements of the body and leg movements based on the salamander’s characteristic morphology. Using a robot, Knüsel et al (2020) were able to reproduce the five motor behaviors observed in salamanders: swimming, struggling, forward underwater stepping, and forward and backward terrestrial stepping. A mathematical model is presented that allows the robot to switch between various motor patterns using a neural circuit with descending brain signals and proprioceptive feedback as input.…”
Section: Robotic Inter-limb Cooridinationmentioning
confidence: 99%
“…The salamander constitutes a model animal for focusing on the following two issues, representing an evolutionary process of moving from water to land: 1) versatile behavior generation against a changing environment, based on CPGs coordinated by both descending signals and sensory feedback; and 2) body-limb coordination, i.e., coordination between undulatory movements of the body and leg movements based on the salamander’s characteristic morphology. Using a robot, Knüsel et al (2020) were able to reproduce the five motor behaviors observed in salamanders: swimming, struggling, forward underwater stepping, and forward and backward terrestrial stepping. A mathematical model is presented that allows the robot to switch between various motor patterns using a neural circuit with descending brain signals and proprioceptive feedback as input.…”
Section: Robotic Inter-limb Cooridinationmentioning
confidence: 99%
“…By adjusting the two input signals to the CPG model, the speed, direction and gait type of the robot can be adjusted, smooth switching from a crawling gait to a swimming gait can be completed, and a turning action can also be completed. Based on the Salamander I robot, a Salamander II robot was established [38]. Using a single CPG circuit, it realized five behaviors: swimming, struggling, forward underwater walking, forward and backward ground walking, and integrated ontology feedback to optimize swimming speed.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, (2012) and Liu et al, (2008) used a CPG to generate bipedal robot locomotion. Also, Habu et al, (2019) used a CPG for a quadruped robot, Knüsel et al, (2020) did for a multi-segmental salamander robot, and Avrin et al, (2017) developed a visual control model of rhythmic ball bouncing using CPG. CPG allows us not only to make a signal with a constant period, but also to change period smoothly with a method of muscle synergy (Aoi et al, 2019), two-layered system (Saputra et al, 2019), and triple-layered system (Qiao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%